Critical criminology - DeKeseredy, Walter S. 1959-; Dragiewicz, Molly (Critical concepts in criminology, 2014)
'Critical Criminology' is now a well-established - if heterogeneous and contentious - field of study. As the field continues to flourish as never before, this title makes sense of the wide range of approaches, theories and concepts that have informed critical criminology